2010
DOI: 10.1111/j.1752-4598.2010.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in light‐attracted chrysomelid populations in a Bornean rainforest

Abstract: 1. Seasonal or annual population fluctuations have been reported for various tropical insect species, exhibiting one or more peaks in abundance at certain times of the year. Such fluctuations have mostly been observed in areas that experience annual wet and dry seasons, and not in areas where climatic fluctuations are unpredictable on an annual basis.2. This study attempted to evaluate the extent of seasonality in population fluctuations of a light-trapped chrysomelid assemblage consisting of 25 Garelucinae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 63 publications
(101 reference statements)
2
20
0
Order By: Relevance
“…To our knowledge, none of the long-term studies have studied correlations between plant phenology and temporal dynamics of tropical insect communities. Among the shortterm studies, no correlation was found between leaf beetle population fluctuations and leaf-flushing phenology in Borneo (Kishimoto-Yamada et al 2010), while the abundance of geometroid moths in Malaysia correlated positively with amount of flowering and leaf-flushing in the previous month (Intachat et al 2001). In addition to seasonal changes, natural populations of short lived organisms also experience annual fluctuations in their abundance, and therefore, tropical insect communities can be expected to change at inter-annual time scales as well.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, none of the long-term studies have studied correlations between plant phenology and temporal dynamics of tropical insect communities. Among the shortterm studies, no correlation was found between leaf beetle population fluctuations and leaf-flushing phenology in Borneo (Kishimoto-Yamada et al 2010), while the abundance of geometroid moths in Malaysia correlated positively with amount of flowering and leaf-flushing in the previous month (Intachat et al 2001). In addition to seasonal changes, natural populations of short lived organisms also experience annual fluctuations in their abundance, and therefore, tropical insect communities can be expected to change at inter-annual time scales as well.…”
Section: Introductionmentioning
confidence: 99%
“…From 1994–1997, the proportion of flushing trees, defined as trees with more than 10% of all crown leaves in the newly developing or immature stages, ranged from 3.8 to 30.1% [23], and flushing trees increased irregularly as 14- and 30-day cumulative rainfall decreased [22,23]. In addition, a number of community-wide synchronous flowering periods, defined as periods during which more than 6% of individual canopy trees undergo flowering, occurred irregularly at intervals of several years, and the number of flowering trees approached zero during non-flowering periods [21,42].…”
Section: Methodsmentioning
confidence: 99%
“…The beetle specimens used for DNA extraction were mounted as voucher specimens and are maintained at Forest Research Centre. The chrysomelids were discriminated into morphospecies and identified on the basis of external characteristics, with reference to a collection of specimens used for previous studies [23,24]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations